2020
DOI: 10.1055/s-0040-1718407
|View full text |Cite
|
Sign up to set email alerts
|

Stoma Closure Improves Head Circumference Growth in Very Preterm Infants after Necrotizing Enterocolitis

Abstract: Introduction Very preterm infants (VPIs) surgically treated for necrotizing enterocolitis (NEC) are at risk of growth retardation. The aim of this study was to demonstrate and compare growth during the first 6 years of life in VPIs with stoma after NEC surgery with VPIs without NEC surgery. Materials and Methods We included all VPIs surgically treated due to NEC at the Odense University Hospital from August 1, 2004, to July 31, 2008. Outcome on growth was compared with a group of VPIs without NEC. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…[15,16] It is reported that in the presence of a stoma, up to 90% of the young children are declining on the growth chart, which is why some advocate early stoma closure. [17][18][19][20] This opinion is supported by the finding that most young children thrive after stoma closure, irrespective of morbidity, weight, or underlying pathology. [17] Considering the increased risk of malnutrition due to stoma morbidity and its impact on growth, it is interesting to see that weight at stoma closure and days until stoma closure were not significantly associated with morbidity following closure in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…[15,16] It is reported that in the presence of a stoma, up to 90% of the young children are declining on the growth chart, which is why some advocate early stoma closure. [17][18][19][20] This opinion is supported by the finding that most young children thrive after stoma closure, irrespective of morbidity, weight, or underlying pathology. [17] Considering the increased risk of malnutrition due to stoma morbidity and its impact on growth, it is interesting to see that weight at stoma closure and days until stoma closure were not significantly associated with morbidity following closure in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to elucidate whether fortification of breast milk with extra protein and calories improves cognitive outcome in infants with more morbidities or impaired growth during hospitalisation. Among infants with NEC excluded from our RCT, Honore et al found HC to be significantly smaller up to 6 month CA [27], stressing the importance of future studies to include groups of severely ill very preterm infants.…”
Section: Discussionmentioning
confidence: 81%
“…Severe restriction (< 3 rd percentile) in weight was most prevalent among surgical NEC patients. We attribute this finding to the high prevalence of intestinal stoma in our cohort (17%), 47 but cannot resolve whether this factor per se contributes to the adverse neurodevelopmental outcomes observed in patients with surgical NEC. 42 Nevertheless, the observed restriction in postnatal growth is especially concerning considering the high rates of treated retinopathy of prematurity, chronic lung disease, and serious brain injury (severe intraventricular hemorrhage, periventricular leukomalacia) among surgical NEC patients.…”
Section: Accepted Manuscriptmentioning
confidence: 84%